2020
DOI: 10.1186/s13071-020-04043-z
|View full text |Cite
|
Sign up to set email alerts
|

Invasive cattle ticks in East Africa: morphological and molecular confirmation of the presence of Rhipicephalus microplus in south-eastern Uganda

Abstract: Background: Rhipicephalus microplus, an invasive tick species of Asian origin and the main vector of Babesia species, is considered one of the most widespread ectoparasites of livestock. The tick has spread from its native habitats on translocated livestock to large parts of the tropical world, where it has replaced some of the local populations of Rhipicephalus decoloratus ticks. Although the tick was reported in Uganda 70 years ago, it has not been found in any subsequent surveys. This study was carried out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 29 publications
(38 reference statements)
7
36
0
Order By: Relevance
“…microplus had never been reported was startling. However, a report by Muhanguzi et al [43] complimented our findings after confirming the presence of Rhipicephalus (B.) microplus ticks in south-eastern Uganda.…”
Section: Discussionsupporting
confidence: 89%
“…microplus had never been reported was startling. However, a report by Muhanguzi et al [43] complimented our findings after confirming the presence of Rhipicephalus (B.) microplus ticks in south-eastern Uganda.…”
Section: Discussionsupporting
confidence: 89%
“…However, recent studies have reported the expansion of the invasive R. microplus in Africa [ 34 ], with reports of it spreading rapidly across West and Central Africa [ 35 ]. This tick has recently been reported in eastern Uganda [ 36 ], confirmed to be present in Kenya and is known to occur in Tanzania and Zambia, where it has largely replaced the indigenous R. decoloratus [ 37 , 38 ]. The wide occurrence and distribution of R. decoloratus ticks across the country explains the observed high prevalence of B. bigemina and A. marginale in different communes within Burundi [ 39 ].…”
Section: Discussionmentioning
confidence: 96%
“…Map showing the location of Sudan in Africa (small map) and the location of the study areas in Sudan (North Kordofan and Kassala states, indicated by orange). Sampling was conducted in Sheikan (1), Al-Rahad (2), Um-Ruwabah (3), West Kassala (4), Kashm el Griba (5), Kassala (6), Aroomah (7) and Wagar (8). The map was created using ArcGIS v. 10 (esri Inc., Redlands, CA, USA).…”
Section: Microorganisms 2020 8 X For Peer Review 3 Of 18mentioning
confidence: 99%
“…Tubes were labelled (location, animal species and date of collection) and sent to the Bundeswehr Institute of Microbiology, Munich, Germany, where ticks were identified to species level using morphological characteristics described by Apanaskevich and Horak [22], Apanaskevich and Horak [23], Apanaskevich and Horak [24], Apanaskevich, et al [25], Voltzit and Keirans [26] and Walker, et al [10,27]. 7and Wagar (8). The map was created using ArcGIS v. 10 (esri Inc., Redlands, CA, USA).…”
Section: Tick Collection and Identificationmentioning
confidence: 99%
See 1 more Smart Citation